Genetic variants of vascular endothelial growth factor predict risk and survival of gliomas - Paulo Linhares; Marta Viana-Pereira; Mónica Ferreira; Júlia Amorim; Rui Nabiço; Filipe Pinto; Sandra Costa; Rui Vaz; Rui Manuel Reis (Tumor Biology)
The vascular endothelial growth factor regulates angiogenesis that is increased in glioma. VEGF polymorphisms are thought to modulate vascular endothelial growth factor plasma levels and therefore may be implicated in glioma risk. We aimed to clarify the role of VEGF and von Willebrand factor polymorphisms in glioma susceptibility and prognosis. A case–control study of 126 glioma patients and 180 cancer-free controls was performed. Using Sequenom MassARRAY platform, 11 VEGF and 1 VWF polymorphisms were genotyped. Unconditional multivariate logistic regression models were used to calculate odds ratios and 95% confidence intervals. The associations between polymorphisms and survival were evaluated using a Cox regression model. Bonferroni’s adjustment was used to correct for multiple testing. The VEGF polymorphism rs833061 was strongly associated with increased risk for glioma (odds ratio = 164.85) and glioblastoma (odds ratio = 155.66), confirmed after Bonferroni correction. Also, the VEGF polymorphisms rs3024994, rs2010963, and particularly the homozygous carriers of rs1005230 were associated with a worse prognosis for glioma and glioblastoma. Our data support a role of VEGF and VWF polymorphisms as glioma biomarkers, with additional potential relevance for molecular stratification of patients for anti-angiogenic therapies.